Psychological distress and workplace risk inequalities among conservation professionals - Thomas Pienkowski; Aidan Keane; Emiel deLange; Vena Kapoor; Munib Khanyari; Roshni Ravi; Izak P. J. Smit; Sofia Castelló y Tickell; Mirjam Hazenbosch; William N. S. Arlidge; Gergő Baranyi; Stephanie Brittain; et al. (Conservation Science and Practice, 2023)
Abstract Workplaces can be sources of both stress and support, affecting employees' mental health and productivity. Yet, little research has investigated variability in workplace risk factors for poor mental health in conservation. We aimed to explore how patterns of psychological distress—a state of emotional disturbance—and associated workplace risk factors vary between conservation job roles. Working with three case study organizations in India, South Africa, and Cambodia, we surveyed 280 field‐based, office‐based, and research staff. Moderate or severe psychological distress was reported by 28.9%. Field‐based practitioners reported a greater imbalance between workplace efforts and rewards (0.35 standard deviation (SD), 95% credibility interval (CI) 0.03–0.67) than their colleagues, which was associated with greater psychological distress (0.24 SD, 95% CI 0.10–0.39). After controlling for this mediated relationship, researchers reported greater psychological distress than field‐based practitioners (0.37 SD, 95% CI 0.02–0.72). However, when accounting for all direct and indirect effects, there was no overall difference in distress between roles. Employers, funders, professional societies, and other institutions seeking to support conservationists' mental health should understand and offer support tailored to role‐specific challenges. Doing so might enhance conservationists' wellbeing while strengthening their ability to reverse global nature loss.